Unlocking Growth: How Knowledge Absorption Drives Innovation in Bali’s Creative Small and Medium Enterprises - Utami, Ni Made Satya; Sanjiwani, Putu Ari Pertiwi; Pramanaswari, A. A. Sagung Istri; Nawanir, Gusman (International Review of Management and Marketing, 2026)
Research Objective: To develop an ACap framework specifically designed for developing countries, MSMEs must master knowledge absorption to drive innovation and transform knowledge into business performance, thereby remaining competitive in the market. This innovative study of 330 economically creative SMEs in Bali reveals an important fact: realized knowledge absorption (RACAP) drives innovation performance 30% more effectively than potential knowledge absorption (PACAP). Using PLS-SEM, we found that superior knowledge absorption is directly associated with greater innovation and business performance. These findings address a critical research gap and provide practical insights for SMEs to enhance their knowledge assets, outperform competitors, and achieve sustainable growth. Conclusions and recommendations: Policymakers and business leaders must understand how SMEs in developing countries can leverage knowledge to achieve true competitive advantage. The impact will be a new paradigm in multidisciplinary research that bridges the gap between knowledge management and business innovation.